How accurate are medical oncologists' impressions of management of metastatic colorectal cancer in Australia?. Issue 2 (16th March 2017) - Au, Lewis; Turner, Natalie; Wong, Hui‐Li; Field, Kathryn; Lee, Belinda; Boadle, David; Cooray, Prasad; Karikios, Deme; Kosmider, Suzanne; Lipton, Lara; Nott, Louise; Parente, Phillip; et al.
Abstract: Aim: Current efforts to understand patient management in clinical practice are largely based on clinician surveys with uncertain reliability. The TRACC (Treatment of Recurrent and Advanced Colorectal Cancer) database is a multisite registry collecting comprehensive treatment and outcome data on consecutive metastatic colorectal cancer (mCRC) patients at multiple sites across Australia. This study aims to determine the accuracy of oncologists' impressions of real‐word practice by comparing clinicians' estimates to data captured by TRACC. Methods: Nineteen medical oncologists from nine hospitals contributing data to TRACC completed a 34‐question survey regarding their impression of the management and outcomes of mCRC at their own practice and other hospitals contributing to the database. Responses were then compared with TRACC data to determine how closely their impressions reflected actual practice. Results: Data on 1300 patients with mCRC were available. Median clinician estimated frequency of KRAS testing within 6 months of diagnosis was 80% (range: 20–100%); the TRACC documented rate was 43%. Clinicians generally overestimated the rates of first‐line treatment, particularly in patients over 75 years. Estimate for bevacizumab in first line was 60% (35–80%) versus 49% in TRACC. Estimated rate for liver resection varied substantially (5–35%), and the estimated median (27%) was inconsistent with the TRACC rate (12%). Oncologists generally felt their practice was similar to other hospitals. Conclusions: Oncologists' estimates of current clinical practice varied and were discordant with the TRACC database, often with a tendency to overestimate interventions. Clinician surveys alone do not reliably capture contemporary clinical practices in mCRC.